2014
DOI: 10.1111/epi.12880
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of epileptic foci in rats using a miniature probe integrating diffuse optical tomography and electroencephalographic source localization

Abstract: SUMMARY Objective The goal of this work is to establish a new dual-modal brain mapping technique based on diffuse optical tomography (DOT) and electroencephalographic source localization (ESL) that can chronically/intracranially record optical/EEG data to precisely map seizures and localize the seizure onset zone and associated epileptic brain network. Methods The dual-modal imaging system was employed to image seizures in an experimental acute bicuculline methiodide rat model of focal epilepsy. Depth infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…ESI was also performed in anesthetized mice using non-invasive 40-channel micro-array EEG, and the accuracy of three inverse solutions—minimum norm estimates (MNE), multiple signal classification, and single dipole fitting—was compared using the boundary-element method based forward model (Lee et al, 2013 ). Integrating a DOT sensor and electrode array in rats, Yang et al ( 2015 ) showed that prior information obtained from the DOT may improve the accuracy of the minimum norm based solution. In a previous study on physical phantom measurements (Yang and Jiang, 2013 ), a significant bias of ESI was observed.…”
Section: Introductionmentioning
confidence: 99%
“…ESI was also performed in anesthetized mice using non-invasive 40-channel micro-array EEG, and the accuracy of three inverse solutions—minimum norm estimates (MNE), multiple signal classification, and single dipole fitting—was compared using the boundary-element method based forward model (Lee et al, 2013 ). Integrating a DOT sensor and electrode array in rats, Yang et al ( 2015 ) showed that prior information obtained from the DOT may improve the accuracy of the minimum norm based solution. In a previous study on physical phantom measurements (Yang and Jiang, 2013 ), a significant bias of ESI was observed.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve reliable source reconstructions, uncertainties in all of the steps have to be treated carefully [12]. Recently, source localization in rodents has been investigated for preclinical and translational research [13], [14]. Various techniques have been used for EEG acquisition: high density scalp EEG cap [13], [15], skull EEG microarray [16], and regular cortical electrode array [14].…”
Section: Introductionmentioning
confidence: 99%
“…Another way to alleviate the ill-conditioning and improve the image quality, involves integrating FMT with other imaging technologies into a hybrid modality. The benefits of this approach have been demonstrated in recent studies for modalities such as CT, MRI, and ultrasound [1621]. Obviously, a miniaturized FMT system offers the potential to combine it with other imaging modalities, especially in the design of miniaturized imaging devices such as endoscopes.…”
Section: Introductionmentioning
confidence: 99%